THE INFLUENCE OF HEALTH EDUCATION WITH FLIP SHEETS MEDIA ABOUT FE TABLETS ON THE LEVEL OF KNOWLEDGE OF PREGNANT WOMEN AT THE SUNGAI RAYA PUBLIC HEALTH CENTER IN KUBU RAYA - Yolanda, Aini; Wijayanti, Wijayanti; Wulandari, Retno (Journal of Advanced Nursing and Health Sciences, 2025)
Background : Anemia in pregnant women is a condition in which the mother has an Hb level of less than 11 gr% as a result of the inability of the red blood cell-forming tissue (erythropoietic) in its production to maintain Hb concentration at normal levels (Ariani et al., n.d., 2022 in Rohani et al., 2023). One important effort in preventing and overcoming anemia is the provision of Fe tablets. Non-compliance of pregnant women in consuming iron tablets can have a greater chance of developing anemia (Astriana, 2017 in Rumiati, 2023). To increase knowledge and compliance in consuming Fe tablets, namely by providing health education or education (Widya, 2021 in Rumiati, 2023). Objective : This study aims to analyze the effect of health education using flipchart media about Fe tablets on the level of knowledge of pregnant women at the Sungai Raya Dalam Kubu Raya Health Center. Method : This study is a Pre-Experimental design study with a one group pretest-posttest method. The population of this study was all pregnant women who underwent pregnancy check-ups at the Sungai Raya Dalam Health Center from July to September 2023, totaling 535 people, while the sample obtained from the calculation results was 53 pregnant women. The sampling technique used was purposive sampling. The data analysis used was the Wilcoxon test. Results : The results of this study indicate that there is an effect of health education with flipchart media about Fe tablets on the level of knowledge in pregnant women with a p-value of 0.000 (p < 0.05). The knowledge of pregnant women before being given health education with flipchart media was sufficient, then after being given health education with flipchart media it was good.